2019
DOI: 10.1200/jco.2019.37.7_suppl.267
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between time to PSA progression (TTPP), radiographic progression-free survival (rPFS) and overall survival (OS) in first-line abiraterone/enzalutamide (Abi/Enza) and docetaxel (Doc) treated patients in a prospective cohort study.

Abstract: 267 Background: Abiraterone, enzalutamide and docetaxel represent first-line (1L) treatment options in mCRPC. A significant correlation between rPFS and OS has been reported for patients treated with 1L abi and enza in mCRPC. It is however unclear whether TTPP or rPFS present a similar magnitude of correlation with OS in Doc-treated pts. Methods: We evaluated the association of TTPP and rPFS with OS in pts treated with 1L Abi/Enza or Doc in a prospective multicenter observational cohort study. TTPP and rPFS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…As expected, both rPFS and TTPP were significantly correlated with OS ( p < 0.001 in both rPFS and TTPP). Importantly, higher SCC in rPFS was observed compared to that in TTPP (0.601 in rPFS vs 0.468 in TTPP), indicating rPFS is a robust surrogate for predicting OS, which is consistent with the previous report by Lorente et al [31].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As expected, both rPFS and TTPP were significantly correlated with OS ( p < 0.001 in both rPFS and TTPP). Importantly, higher SCC in rPFS was observed compared to that in TTPP (0.601 in rPFS vs 0.468 in TTPP), indicating rPFS is a robust surrogate for predicting OS, which is consistent with the previous report by Lorente et al [31].…”
Section: Discussionsupporting
confidence: 90%
“…Several post-hoc studies from the results of randomized control trials (RCTs) revealed emerging evidence that radiographic progression-free survival (rPFS) is highly correlated with overall survival (OS), potentially serving as an indicator of treatment outcome in CRPC patients [29,30,31]. In 2015, Morris et al first reported that the Spearman’s correlation coefficient (SCC) between rPFS and OS was 0.71 (95%CI: 0.65–0.77) in pot-hoc analysis from COU-AA-302 study (abiraterone vs placebo for chemotherapy-naïve metastatic CRPC) [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the emphasis on radiographic results to determine disease progression and treatment benefit in the mCRPC setting does not adequately reflect clinical practice, which involves a broader and more holistic assessment of determining treatment benefit. While there are data emerging that rPFS is a predictor of OS, [54][55][56] CADTH reviewers concluded that the association was difficult to interpret at the time of this review because of the varying definitions of rPFS used, relatively short follow-up periods used for the comparisons, and lack of prospective evidence. The clinical experts agreed that given the advancements in therapies and understanding of the natural history of prostate cancer, OS remains the most clinically relevant outcome.…”
Section: External Validitymentioning
confidence: 98%